Essential oil composition of Pentzia incana (Asteraceae), an important natural pasture plant in the Karoo region of South Africa. Issue 2 (29th June 2018) - Hulley, Isabel M; Sadgrove, Nicholas J; Tilney, Patricia M; Özek, Gulmira; Yur, Suleyman; Özek, Temel; Başer, Kemal Hüsnü Can; van Wyk, Ben-Erik
Abstract : Pentzia incana is one of the most important of all natural pasture plants in the dry interior (Karoo) region of South Africa. This highly aromatic shrub is thought to be responsible for the distinctive flavour of Karoo lamb (a registered geographical indication), yet the essential oil is here characterised for the first time. Leafy twigs are traditionally chewed for relief of stomach ache. Essential oil is associated with numerous small, multicellu- lar glands. Gas chromatography and gas chromatography/mass spectrometry analysis of 17 essential oil samples from five populations showed considerable variation in both yield (0.12% to 0.88% dry weight) and composition. Of interest was the presence of one major biosynthetic group comprising yomogi alcohol (to 38.9%), artemisia alcohol (to 26.1%), artemisia ketone (to 35.0%) and artemisyl acetate (to 9.4%). High levels of fragranol (26.9%) and fragranyl acetate (27.1%) were observed only in a single specimen. Other main compounds were 1, 8-cineole (to 16.7%), santolina alcohol (to 11.3%), camphor (to 47.9%), linalyl acetate (to 17.4%) and bicyclogermacrene (to 11.8%). Six of the 10 major compounds were isolated and their identities confirmed by nuclear magnetic resonance. The volatile compounds may possibly be linked to the medicinal use of P. incana, as well as the flavour profile of Karoo lamb.